Compare the Mean Duration of Healing with Sodium Carboxylic Methyl- Cellulose Silver Dressing Versus Standard Petroleum Gauze Dressing for Management of Second-Degree Burns - Ekramuddin, Umama Jailani, Hamza Fayyaz, Zarak Khan, Hamza Khan Shehbazi, Sayed Rafaiuddin Haider, Shazma (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Burn injury is one of the most devastating and serous form of trauma that man sustains. Millions of people all over the world are hospitalized each year for treatment of burns and thousands die. It is estimated that in UK alone 10000 burn victims are hospitalized each year and 700 die. Objective: To compare the mean duration of healing with sodium Carboxylic methyl- cellulose silver dressing versus standard petroleum gauze dressing for management of second-degree burns. Material and methods: A total of 100 patients of second-degree burns were selected for this study. Clinical examination of patients was done to find out the degree of burns. In group A, Aquacel Ag dressing was applied. In group B, petroleum gauze dressing was applied. Patients were evaluated on each visit when dressing was changed for complete healing. Results: The mean age of the patients was 33.4±19.2 years. Duration of healing when compared in both the groups its showed that average time of healing in group A was 10.38+2.71 while in Group B it was 13.48+5.26SD and it showed significant difference with p-value=0.000. Practical Implications: This study will help to find the best method used for healing in second-degree burns. Conclusion: Mean duration of healing with sodium Carboxylic methyl-cellulose silver dressing was less than petroleum gauze dressing for management of second-degree burns. Keywords: Burn, Injury, Tissue, Wound, Healing, Management, Dressing